2014
DOI: 10.1134/s0036024414120437
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of carbon nanotubes/BiOBr composites with higher visible light photocatalytic activity

Abstract: A novel flower like photocatalyst CNTs/BiOBr was successfully prepared by a facile hydrothermal method. The morphology and the physicochemical properties of the prepared samples were investigated using scanning electron microscopy (SEM), X ray diffraction (XRD), energy dispersive X ray spectrometry (EDX), and UV-visible diffuse reflectance spectroscopy (UV-vis DRS). The photocatalytic activity was evaluated by degradation of Rhodamin B (RhB) dye. It was demonstrated that CNTs/BiOBr photocatalyst could effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Meanwhile, in comparison with aromatic organics, straight-chain alkanes are well known for being more difficult to be photocatalytically degraded [18]. Hence, to more efficiently utilize the solar light and enhance the activity of Bi-OBr toward gaseous alkanes, several methods have been attempted, including metal deposition [19,20], metal oxide composition [21,22] and carbon material immobilization [23,24]. Among these methods, the in-situ decoration of metallic Bi on BiOBr is considered as a facile operational method.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in comparison with aromatic organics, straight-chain alkanes are well known for being more difficult to be photocatalytically degraded [18]. Hence, to more efficiently utilize the solar light and enhance the activity of Bi-OBr toward gaseous alkanes, several methods have been attempted, including metal deposition [19,20], metal oxide composition [21,22] and carbon material immobilization [23,24]. Among these methods, the in-situ decoration of metallic Bi on BiOBr is considered as a facile operational method.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the bismuth oxybromides and their photocatalytic properties have been studied . There are three types of BiOX‐based (X=Cl, Br, I) composite photocatalysts: semiconductor/BiOX (X=Cl, Br, I) composite photocatalysts, metal/BiOX(X=Cl, Br, I) composite photocatalysts and sensitized BiOX(X=Cl, Br, I) composite photocatalysts . The most widely studied BiOX‐based (X=Cl, Br, I) composite photocatalysts have been the semiconductor/BiOX (X=Cl, Br, I) composite photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] There are three types of BiOX-based (X = Cl, Br, I) composite photocatalysts: semiconductor/BiOX (X=Cl, Br, I) composite photocatalysts, [10][11][12] metal/BiOX(X=Cl, Br, I) composite photocatalysts [13][14][15][16][17][18][19][20][21][22][23][24][25][26] and sensitized BiOX(X=Cl, Br, I) composite photocatalysts. [27][28][29][30][31][32][33][34][35] The most widely studied BiOX-based (X = Cl, Br, I) composite photocatalysts have been the semiconductor/BiOX (X=Cl, Br, I) composite photocatalysts. For example, Dai et al [36] prepared TiO 2 /BiOI composite photocatalyst with p-n junction.…”
Section: Introductionmentioning
confidence: 99%
“…To explain the synergetic effects suggestion was made that both members of a photo generated electron hole pair are consumed in separate redox half reactions preventing recombina tion of the electron hole pair [6]. The use of photoca talysis, induced by visible light to remove simulta neously an organic substance and metal ions from pol luted water, attracted the attention of investigators [7][8][9][10][11][12]. In our earlier work [13][14][15][16][17], we found that by using poly(fluorene co thiophene) modified TiO 2 (PFT/TiO 2 hereafter) with visible light it is possible to prepare a good photocatalyst capable to remove inor ganic and organic pollutants from wastewater.…”
mentioning
confidence: 99%